The black history book - Blyden, Nemata Amelia, 1964-; Akpan, Paula; Harper, Mireille, 1995-; Lockhart, Keith; Maddox, Tyesha; Njoku, Raphael Chijioke; Pepera, Luke; Swainston, George; Walker, Robin, 1967-; Wilson, Jamie Jaywann; Olusoga, David (Big ideas simply explained., 2021)
Discover the rich and complex history of the peoples of Africa, and the struggles and triumphs of Black cultures and communities around the world.